Laporan tahunan / Bidang Permuseuman, Sejarah dan Kepurbakalaan, Kantor Wilayah Departemen Pendidikan dan Kebudayaan Propinsi Nusa Tenggara Barat
Annual report of the field of archeology, history, and museum of Propinsi Nusa Tenggara Barat regional office, Dept. of Education and Culture.